Glycosyl-phosphatidylinositol-anchored and transmembrane forms of CD46 display similar measles virus receptor properties: virus binding, fusion, and replication; down-regulation by hemagglutinin; and virus uptake and endocytosis for antigen presentation by major histocompatibility complex class II molecules. - Varior-Krishnan, G (1994)
The CD46 molecule is a receptor for measles virus (MV), CD46, which protects autologous cells from complement-mediated damage, exists in several isoforms which are variably expressed in different human tissues. These isoforms differ in their cytoplasmic and transmembrane regions and in a small portion of their proximal extracytoplasmic regions. To examine the role of the cytoplasmic and transmembrane regions of CD46 in MV infection, mouse M12 B cells stably expressing a transmembrane or a chimeric glycosyl-phosphatidylinositol (GPI)-anchored form of CD46 (CD46-GPI) were used. Both the GPI-anchored and transmembrane CD46 forms were able to mediate MV binding. MV binding mediated by the GPI-anchored form but not that mediated by the transmembrane form was abolished after treatment with phosphatidylinositol phospholipase C. MV infection of both M12.CD46 and M12.CD46-GPI cells but not parental M12 cells resulted in MV replication. Expression of hemagglutinin induced cell surface down-regulation of both CD46 and CD46-GPI. Both M12.CD46 and M12.CD46-GPI cells were able to efficiently capture MV for presentation of viral antigens by major histocompatibility complex class II molecules to T cells. This presentation was blocked by chloroquine, indicating some virus endocytosis. These data imply that the extracytoplasmic region encompassing the four N-terminal invariable short consensus repeat regions of CD46 is sufficient to act as a receptor for MV and that the cytoplasmic and transmembrane regions of CD46 may not play a major role in the signal for the hemagglutinin-induced down-regulation of CD46 and/or endocytosis of MV.